The impact of government decentralisation on the development and implementation of benefit-sharing laws in Kenya's extractive sector - Singoei, Abraham Korir (Department of Private Law, 2022)
Intra-state distribution of monetary and non-monetary benefits from resource extraction among multiple entities is a subject of considerable interest in natural resource law. Drawing mainly but not exclusively from international human rights and environmental law, this study explores the nature, core content and models of benefit sharing in the extractive sector in Kenya. The study establishes that central to the push for benefit sharing is the desire to realise justice – commutative, distributive or compensatory – for resource-host communities and regions. Kenya is an ideal case study related to benefit sharing because of its recent adoption of multi-level governance known as devolution. From this lense of multi-level governance, the thesis assesses whether such a system aids or impedes the effective distribution of resource benefits to host regions and communities, a factor critical to mitigating resource conflict. The thesis examines Kenya's legal regime governing benefit sharing from the colonial period to the present. This historical review demonstrates the significant impact that Kenya's Constitution adopted in 2010 has produced in entrenching benefit sharing in the norms and institutions of the state. It attributes the enhanced legal and policy recognition of benefit sharing not merely to the text of the Constitution but to the role played by semi-autonomous territorial units, known as counties, in shaping emerging norms and standards on benefit-sharing through a wide range of strategies including legislation, litigation and information dissemination. Where countiestake a proactive role in shaping the manner in which resource costs and benefits are distributed in law, responsive legislative outcomes can be realised. Conversely, where counties fail to seize their institutional position to aid resource impacted communities' engagement with policy opportunity structures, national institutions and resource operators are likely to default to historically exclusionary and paternalistic approaches to benefit sharing. The legal and institutional gaps evident in Kenya's mineral and petroleum legislative regime are largely a function of this dynamic. In examining the response of two resource-host counties in Kenya-Turkana and Kwalethe study demonstrates the need for counties to make pro-community policy choices in ensuring that constitutionally mandated monetary and non-monetary benefits are accessed at the local level. The study validates the utility of benefit sharing as an enabler of stable resource development environment especially when its impact is experienced through local economic development within host regions and communities.